Analysis the Potential of Media to Promote a Cosmopolitan Orientation through the Two Media Formats: Television and News - Zhang, Yun (Journal of Theory and Practice of Social Science, 2024)
This paper is centred around Robertson's (2019) argument that the possibility of media having the ability to inspire cosmopolitan tendencies is "both inevitable and impossible". The key focus is on analysing two communication media, television and the news, to analyse the extent to which they promote cosmopolitanism. In the end, it is found that Robertson's argument is indeed valid, but that diasporic media have the potential to become alternative spaces for world solidarity.